Cardiovascular Effects of Diabetes Mellitus: A Review of Pathophysiology and Management - Omar Elsaka (Journal of Clinical and Preventive Cardiology)
Diabetes mellitus presents a significant global health challenge by substantially increasing the risk of developing cardiovascular disease (CVD). This review delves into the pathophysiological mechanisms that underlie this association, exploring the contributions of chronic hyperglycemia, insulin resistance, and other factors to the development and progression of CVD in individuals with diabetes. Furthermore, the review evaluates current management strategies, including glycemic control, blood pressure management, lipid management, and antiplatelet therapy, emphasizing their critical role in mitigating cardiovascular risk and improving patient outcomes.